2022
DOI: 10.1155/2022/4661108
|View full text |Cite|
|
Sign up to set email alerts
|

A Novel Model to Detect and Classify Fresh and Damaged Fruits to Reduce Food Waste Using a Deep Learning Technique

Abstract: Due to a lack of efficient measures for dealing with food waste at many levels, including food supply chains, homes, and restaurants, the world’s food supply is shrinking at an alarming pace. In both homes and restaurants, overcooking and other factors are to be blamed for the majority of food that is wasted. Families are the primary source of food waste, and we sought to reduce this by identifying fresh and damaged food. In agriculture, the detection of rotting fruits becomes crucial. Despite the fact that pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Our method achieves high accuracy and outperforms several recently published works [5,19,20,[23][24][25] due to intelligent selection of the AlexNet architecture. Our study indicates that the training time of AlexNet architecture is five times faster as compared to others deeper architecture speed.…”
mentioning
confidence: 54%
See 3 more Smart Citations
“…Our method achieves high accuracy and outperforms several recently published works [5,19,20,[23][24][25] due to intelligent selection of the AlexNet architecture. Our study indicates that the training time of AlexNet architecture is five times faster as compared to others deeper architecture speed.…”
mentioning
confidence: 54%
“…The authors concluded that the SVM the achieved highest 99% classification accuracy than the compared methods. In [19], fruit classification was achieved by using CNN and Softmax, which yielded 97.14% accurate classification.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…The fully connected (Fc) layers were composed of 512, 128, 64, 32, and 4 neurons, respectively. To convert the DCNN output into probabilities for each category, a softmax function was introduced to the activation function of Fc5 ( Kumar et al., 2022 ). The categorical cross-entropy loss function was employed to measure the distance between the probability distribution of the DCNN output values and the true values.…”
Section: Methodsmentioning
confidence: 99%